Costume no livro I do Tratado da natureza humana de David Hume - Stephanie Hamdan Zahreddine (2013)
This study aims to analyze the concept of custom or habit in Book I of Humes Treatise of Human Nature. The interpretative tradition acknowledges the relevance of this concept to Humes theory especially in the context of Humes analysis of causality and in the widely known problem of induction , but rarely deals with the investigation of other fields of customs influence. Even in the context of causality, the independent and thorough study of custom is scarce. In this scenario, we develop an analysis of custom, according to Hume, that includes: i) its conceptual study the words custom and habit have nuances in Humes approach which are distinct from both the dictionary definitions and the approaches of Humes philosophical predecessors; ii) the examination of its role in a) the formation of abstract ideas, b) causality, c) general rules, and d) in the belief in the existence of the external world, which are basic processes of humans epistemic constitution. After this analysis, developed in chapter I and II of the thesis, in chapter III: iii) we emphasize a) the prescriptive dimension of Humes epistemological use of custom, which allows us to differentiate between customs reliable and unreliable effects. This opens the way to finding b) its foundational status in the knowledge of matters of fact.